1997
DOI: 10.1046/j.1365-3059.1997.d01-59.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonate transport in Phytophthora capsici

Abstract: Phosphate was shown to reverse the in vitro activity of phosphonate ions against P. capsici (strain 375) more efficiently in liquid than in solid media. Phosphonate transport by mycelia incubated in aqueous solutions was enhanced by a previous phosphate starvation and the presence of K þ cations. The intracellular phosphonate concentration reached a constant level and this concentration, which is a function of the external concentration, fits a hyperbolic relationship. Phosphonate transport was greatly stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Darakis et al . () concluded the presence of K facilitated phosphite uptake into Phytophthora capsici hyphae. If mycelial growth suppression is used as an indicator of increased phosphite assimilation, then this enhanced assimilation of phosphite in the presence of K may have occurred, as KH 2 PO 3 produced statistically significantly ( P < 0.05) greater inhibition compared to H 3 PO 3 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Darakis et al . () concluded the presence of K facilitated phosphite uptake into Phytophthora capsici hyphae. If mycelial growth suppression is used as an indicator of increased phosphite assimilation, then this enhanced assimilation of phosphite in the presence of K may have occurred, as KH 2 PO 3 produced statistically significantly ( P < 0.05) greater inhibition compared to H 3 PO 3 .…”
Section: Discussionmentioning
confidence: 97%
“…B€ ucking & Heyser (1999) stated that the presence of K facilitates the uptake of mobile polyphosphate into fungal cells, maintaining that it helps retain the charge balance and pH of the fungal cell and is the counter ion to the transport of polyphosphates into the vacuole. Darakis et al (1997) concluded the presence of K facilitated phosphite uptake into Phytophthora capsici hyphae. If mycelial growth suppression is used as an indicator of increased phosphite assimilation, then this enhanced assimilation of phosphite in the presence of K may have occurred, as KH 2 PO 3 produced statistically significantly (P < 0.05) greater inhibition compared to H 3 PO 3 .…”
Section: Discussionmentioning
confidence: 98%
“…Fosetyl-Al (ALI) is a phosphonate that demonstrated antimicrobial effects when used to treat infections caused by various microorganisms (Darakis et al, 1997; Panicker and Gangadharan, 1999). Several studies demonstrated that the mode of action of phosphonates can alter fungal metabolism (Guest and Grant, 1991) and cell morphology (Jiang, 1990; Jiang and Grossmann, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, increasing concentrations of AG3 phosphonate inhibited the growth of P. capsici on V8 agar medium but not in solutions. These results may be partly explained by the fact that P. capsici is known as one of the phosphonate-tolerant species in the genus Phytophthora (Bompeix & Saindrenan, 1984;Darakis et al, 1997). The concentration of phosphate in the medium can also have an effect on in vitro toxicity of phosphonate (Bompeix & Saindrenan, 1984;Darakis et al, 1997).…”
Section: Effect Of Ag3 Phosphonate On Phytophthora Blight Of Bell Pepmentioning
confidence: 99%
“…These results may be partly explained by the fact that P. capsici is known as one of the phosphonate-tolerant species in the genus Phytophthora (Bompeix & Saindrenan, 1984;Darakis et al, 1997). The concentration of phosphate in the medium can also have an effect on in vitro toxicity of phosphonate (Bompeix & Saindrenan, 1984;Darakis et al, 1997). Whether the effect of AG3 phosphonate against the P. capsici is direct or indirect, control of damping-off or root rot of cucumber or phytophthora blight of bell peppers was evident in the peat-based substrate or sandy-loam soil artificially infested with the soil inoculum of the pathogen.…”
Section: Effect Of Ag3 Phosphonate On Phytophthora Blight Of Bell Pepmentioning
confidence: 99%